EFL Teachers’ Perceptions on ICT in English Classroom - Farhan Fauzia; Rajji K. Adireja; Yustika Nur Fajriah (Institut Pendidikan Indonesia Garut, 2021)
Digital technology has permeated almost every aspect of life. Meanwhile, the responses from the field of language teaching in Indonesia to this new development have been scarce. This study aims to investigate the EFL teachers’ perceptions on ICT in English classrooms. To achieve this aim, a qualitative case study design with a semi-structured interview as the instruments was employed. The participants involved in this research were two English teachers in one of senior high schools in Garut. In conclusion, both participants had a positive perception about the use of ICT in English classrooms. This is indicated by their knowledge of ICT, the kind of ICT, the benefits of ICT, the role of ICT, and how to use it. In addition, they also supported the existence of ICT in English Classroom which is claimed to be helpful. However, they still had barriers in applying ICT in their classroom technically and non-technically